Safety in psychiatric inpatient care: The impact of risk management culture on mental health nursing practice - Slemon, Allie (Nurs Inq, 2017)
The discourse of safety has informed the care of individuals with mental illness through institutionalization and into modern psychiatric nursing practices. Confinement arose from safety: out of both societal stigma and fear for public safety, as well as benevolently paternalistic aims to protect individuals from self‐harm. In this paper, we argue that within current psychiatric inpatient environments, safety is maintained as the predominant value, and risk management is the cornerstone of nursing care. Practices that accord with this value are legitimized and perpetuated through the safety discourse, despite evidence refuting their efficacy, and patient perspectives demonstrating harm. To illustrate this growing concern in mental health nursing care, we provide four exemplars of risk management strategies utilized in psychiatric inpatient settings: close observations, seclusion, door locking and defensive nursing practice. The use of these strategies demonstrates the necessity to shift perspectives on safety and risk in nursing care. We suggest that to re‐centre meaningful support and treatment of clients, nurses should provide individualized, flexible care that incorporates safety measures while also fundamentally re‐evaluating the risk management culture that gives rise to and legitimizes harmful practices.